Development of E-module Space Geometry Based on Vee's Heuristic Strategy to Train Students' Mathematical Representation Skills - Aidah Murdikah; Syamsuri Syamsuri; Hepsi Nindiasari; Novaliyosi Novaliyosi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
The research aims to produce e-modules based on vee heuristic strategies that are valid, practical, and effective to train the mathematical representation skills of high school students, with the material used is the geometry of space. This research is development research with 4-D design (Define, Design, Development, and Dissemination). The subjects of this study were students of class XII MIPA and IPS Of Al-Qudwah Integrated High School, which amounted to 30 students. The data in this study was collected using questionnaires and tests. From the analysis results obtained, the average total validation score (RTV) from media experts is 4,062 with an excellent category, material experts with 4,625 with unique varieties, and the average e-module user response score of 89.00. The indicates that the student's response to Learning using e-modules based on heuristic vee strategies is positive so that e-modules can be declared practical. The mathematical representation of students after using this vee heuristic strategy-based e-module earns a total average of 3.32 with excellent category. Based on the results of such data analysis, the e-module based on vee heuristic strategies developed is worth using as a practical learning resource to train students' mathematical representation skills on space geometry. The app makes it easy for students to access flexible learning resources anywhere and anytime.